John Ruskin, William Morris and Walter Pater: From Nature to Musical Harmony in the Decorative Arts - Martine Lambert-Charbonnier (Cahiers Victoriens et Edouardiens)
John Ruskin’s claim that what is essential in all art is to fashion by hand what the eye sees clearly, blurred the divide between the fine arts and the decorative arts. Advocating a renewed experience of nature proper to disclose truth to the beholder, he inspired William Morris with a new form of interior design that promoted craftsmanship as a way to counter mass production and restore man’s dignity. The revival of the gothic style was for him a way to renew Victorian culture by emphasizing the close observation of nature, as well as the values of craftsmanship. While the decorative arts created an environment conducive to a better appreciation of natural beauty, they also sheltered the aesthete from the ugliness of the industrial age. Patterns designed by Morris were loved by aesthetes who wanted their homes to mirror their dreams and aspirations and who embraced Walter Pater’s epicurean aesthetics. Pater’s celebration of music in The Renaissance as the ideal towards which all arts aspire, fostered the idea of interior design as a musical composition enhancing pure perception for the aesthetic mind. The essay examines to what extent aesthetic interiors show this ambiguity between the desire to re-discover natural beauty and truth and the retreat into aesthetic dreams.